PEMBERIAN REMISI TERHADAP NARAPIDANA TINDAK PIDANA KORUPSI BERDASARKAN PERATURAN PEMERINTAH NOMOR 99 TAHUN 2012 TENTANG SYARAT DAN TATA CARA PELAKSANAAN HAK WARGA BINAAN PEMASYARAKATAN DIKAITKAN DENGAN HAK ASASI MANUSIA TERPIDANA - Adhani, Yuni Aditya; ', Erdianto; ', Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Republic of Indonesia is state based on law. The purpose of law is to reach the better life in society. If some one do something which is crime, then he will be punish. Basically the punishment is not only to give affliction to one person or more but there is a guidance from the state. Punishment to criminal carried in correctional institution.In corecctional institution, convicted criminal here right appropriate with Subsection 14 clause (1) latter i Undang-Undang Nomor 12 Tahun 1995 about Pemasyarakatan that at one of rights for convicted criminal is get reduced period the (Remition). Remition given is the convicted criminal rights that have to give from state if the convicted criminal already fulfill the reguirement that has been specified in the regulation.But in the Peraturan Pemerintah Nomor 99 Tahun 2012 about Syarat dan Tata Cara Pelaksanaan Hak Warga Binaan Pemasyarakatan has been strictly about remition given to corruption case convicted criminal, this point is prejudice those convicted criminal. This case related with yurisdiction wich is the function of correctional institution do founding in order to the convict criminal can get their right which is the remition appropriately with correctional system in Indonesia.Stricting the remition given to corruption case convicted criminal are not suitable with the lex of human right. One of example is contradict which is in constitution state in “every one has the right to get equality before the law and get legal certainty and same treat before the law”.Key Words : Remition – Corruption Case Criminal – Human Right